Muhammad Abduh : Meninjau Peran dan Kepemimpinan Dalam Akhbar al-Waqā’i‘ al-Misrīyyah - Amir, Ahmad Nabil; Rahman, Tasnim Abdul (Pascasarjana IAIN Metro, 2024)
This article reviews the role and leadership of Muhammad Abduh (1849-1905) in his career as editorial head of the newspaper al-Waqā'i' al-Misrīyyah (الوقائع المصرية) since 1880. His actions in the realm of journalism are important in the context of the rise of the Egyptian newspaper, especially al -Mu'ayyad and al-Waqā'i' al-Misrīyyah as official government newspapers to develop modernist ideals and influence public opinion in Egypt. It made an important impact which enabled it to play a role in developing the dignity of the language, increasing the influence of the press and journalism and raising public awareness of the intense political and cultural interactions in the development of the spirit of nationalism and social consciousness in Egypt. His political writings and plans cover the periods of Riyad Pasha's administration, Sharif's administration and times of upheaval. This article highlights the ideas he expressed regarding social and spiritual renewal, as well as related educational, religious and socio-cultural issues. The study method is based on documentation and bookkeeping methods. The study data was reviewed descriptively, analytically and comparatively. The conclusion of the study finds dynamic and productive developments during Abduh's leadership leading to the al-Waqa'i' al-Misriyyah newspaper which succeeded in raising society's problems and drawing awareness about the latest developments in the world of politics and newspapers as well as maintaining the ethical interests and values of journalism.